The experience of newly qualified clinical psychologists within the NHS subject to a complaint. - Hogben, Naomi; Robertson, Noelle (Ethics & Behavior)
This study aimed to investigate the experience of UK-based, NHS-employed clinical psychologists subject to a complaint during their first five years after qualification, with a particular focus on the complaint's impact on professional development. Semi-structured interviews were conducted with 10 volunteer participants, with data analyzed utilizing thematic analysis. The analysis revealed two superordinate themes, that of 'System Indifference', and 'I am a good clinician?' These themes reflected the significant and aversive impacts of receiving a complaint early in a career at a time when professional identity is forming and fragile. Themes also revealed that these early career clinicians experience marked isolation, and we suggest that structured support offering emotional containment and practical advice post-complaint is essential.